Orientasi Kepatutan Sosial dan Respons Tipuan pada Alat Ukur dalam Konteks Seleksi Kerja - Widhiarso, Wahyu (Universitas Muhammadiyah Surakarta, 2011)
This study examined the correlation between social desirability with the magnitude of the individualsâ intensity to fake their responses on personality measurement in the context of job selection. Social desirability bias is defined as the tendency of individuals to give a response in a certain manner that will be viewed favorably by others. 90 students participated in the quasi experimental under within-subject design with two occasions. At the first occasion, participants were asked to complete the five-factor personality scale in an honest way (neutral condition) whereas in the second occasions they were asked to complete as if they are applicants who follow the employment selection (motivational condition). Intensity of faking was operationalized by the differences between both conditions. Data analysis suggests three findings: (a) personality measurement using self-reported techniques was vulnerable to faking when applied to employment selection. (b) There are individual differences in the amount of faking. (c) Social desirability can explain these individual differences, with the effect size between 2% to 20%. This study recommends that the using instrument to measure personality should be modified before it was applied to the selection process with respect to content of indicators and the impact of social desirability